2018
DOI: 10.3390/ijerph15112554
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Terror and Psychological Well-Being: The Moderating Role of Emotional Intelligence

Abstract: The purpose of this study was to empirically explore whether or not the level of emotional intelligence of adolescents mitigates the potential adverse effects of the fear of terror on their psychological well-being. Data for this study were collected through a voluntary survey from a sample of 385 adolescents residing in the terrorism-affected provinces of Pakistan: Khyber Pakhtunkhwa (KPK) and Balochistan. The results from the structural equation modeling revealed that fear of terrorism had a significant nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 71 publications
2
15
0
2
Order By: Relevance
“…Subjective well-being signifies aspects of the effect of life satisfaction decisions [96]. The results of the fear and psychological well-being are aligned with the past studies of Asad et al [97] and Dumalaon-Canaria et al [98].…”
Section: Research Sample and Data Collectionsupporting
confidence: 84%
“…Subjective well-being signifies aspects of the effect of life satisfaction decisions [96]. The results of the fear and psychological well-being are aligned with the past studies of Asad et al [97] and Dumalaon-Canaria et al [98].…”
Section: Research Sample and Data Collectionsupporting
confidence: 84%
“…It is also negatively correlated with social anxiety [107], cybervictimization, and suicide risk [111]. It can even dampen the negative impact of very intense emotions on psychological well-being, such as the fear of terrorism in adolescents living in high-risk areas [112].…”
Section: Self-esteem and Gifted Studentsmentioning
confidence: 99%
“…Emotional intelligence controls the negative affectivity by lowering its symptoms such as aggression and anger [56]. The theory of Salovey and Mayer [124] claims that emotional intelligence positively predicts the PWB of employees because it holds the flow of negative emotions and nourishes optimism [12,30,33,127]. The finding of studies has also shown that emotional intelligence moderates the impact of negative emotions that occurs due to negative experience [43,77].…”
Section: Perceived Organizational Politics Negative Affectivity Andmentioning
confidence: 99%